Application of 2-D GDQ Method to Analysis a Thick FG Rotating Disk with Arbitrarily Variable Thickness and Non-Uniform Boundary Conditions (Advances in Applied Mathematics and Mechanics, 2024)
In this paper two-dimensional differential quadrature method has been usedto analyze thick Functionally Graded (FG) rotating disks with non-uniform boundaryconditions and variable thickness. Material properties vary continuously along bothradial and axial directions by a power law pattern. Three-dimensional solid mechanicstheory is employed to formulate the axisymmetric problem as a second order systemof partial differential equations. The non-uniform boundary conditions are exerted directly into the governing equations to reach the eigenvalue system of equations. Fourdifferent disk profile shapes are considered and discussed. The effect of the powerlaw exponent is also investigated and results show that by the use of material whichfunctionally varied along the radial and especially axial directions the stresses andstrains can be controlled so the capability of the disk is increased. Comparison withother available approaches in the literature shows a good agreement here in terms ofcomputational time, robustness and accuracy of the present method. Moreover, novelapplications are shown to provide results for further studies on the same topics.